UNDERSTANDING STUDENTS’ MATHEMATICAL COMMUNICATION AND SELF-CONFIDENCE: IMPLICATIONS FOR STUDENT-CENTERED MATHEMATICS CLASSROOMS - Annisa Desti Fahjri; Siti Fatimah; Tatang Herman (ALGORITMA: Journal of Mathematics Education, 2026)
Abstract Mathematical communication and self-confidence are essential components of mathematics learning, yet many students still struggle to express mathematical ideas and lack confidence in communicating their opinions. This study aims to analyze students’ mathematical communication skills and self-confidence and explore the pedagogical factors influencing these outcomes. A mixed-methods approach with an exploratory sequential design was employed involving eighth-grade students from a junior high school in Bandung. Data were collected through a self-confidence questionnaire, a mathematical communication test, and semi-structured interviews, and analyzed using quantitative and qualitative methods. The findings indicate that most students demonstrated moderate levels of mathematical communication (82.76%) and self-confidence (65.51%). Interviews revealed that limited classroom participation, fear of making mistakes, and teacher-centered instruction hindered the development of both skills. These findings highlight the importance of implementing more participatory, student-centered pedagogical practices to foster students’ mathematical communication and self-confidence. Abstrak Komunikasi matematis dan kepercayaan diri merupakan komponen penting dalam pembelajaran matematika, tetapi banyak siswa masih kesulitan mengungkapkan ide matematis dan kurang percaya diri saat menyampaikan pendapat. Penelitian ini bertujuan menganalisis kemampuan komunikasi matematis dan kepercayaan diri siswa serta mengeksplorasi faktor-faktor pedagogis yang memengaruhinya. Penelitian menggunakan pendekatan mixed methods dengan desain exploratory sequential yang melibatkan siswa kelas VIII di salah satu SMP di Kota Bandung. Data dikumpulkan melalui angket, tes, dan wawancara semi-terstruktur, kemudian dianalisis secara kuantitatif dan kualitatif. Hasil menunjukkan bahwa sebagian besar siswa berada pada kategori sedang dalam kemampuan komunikasi matematis (82,76%) dan kepercayaan diri (65,51%). Wawancara mengungkap bahwa rendahnya partisipasi, ketakutan melakukan kesalahan, dan pembelajaran yang berpusat pada guru menghambat perkembangan kedua aspek tersebut. Temuan ini menegaskan pentingnya praktik pembelajaran yang lebih partisipatif dan berpusat pada siswa untuk mengembangkan komunikasi matematis dan kepercayaan diri.